Trajectories of Development and Socialization of Trans Brazilian Youth Through Self-Portraits - Cerqueira-Santos, Elder; de Santana, Mariana Valadares Macêdo; de Miranda Ramos, Mozer (Frontiers in Psychology, 2020)
The aim of this research was to explore the meanings of childhood memory established by young people who identify themselves as trans. In a chauvinistic country such as Brazil, sexual socialization of non-cisgender youth is beset by unique challenges, such as discrimination and violence. This study was based on the proposal of a self-portrait method as a content trigger in interviews with three trans young women who reported their life stories. We analyzed data using the oral story technique, through which the described themes came up. The results present developmental narratives related to gender issue from childhood, which reflected on the experience of youth. Reports of discrimination based on the image of others (family, school and community) about the gender development of the participants and their relationship with their bodies stand out. We see the importance of reflecting on life history memories in trans identity in order to give meaning to this experience. The influence of heteronormative and sexist Brazilian culture is noticed in the participants' reports.